Elective course program on comprehensive dental care in patients with bleeding disorders - Alvarez Hernández, José Carlos (2022)
Introduction: Coagulation disorders arise as a consequence of a group of alterations that are triggered during the coagulation process, hence the need imposed on the professional training of the dentist to establish adequate care for patients who comprise this population group. Objective: to develop an elective course program on comprehensive dental care in patients with coagulation disorders. Material and Methods: A qualitative and descriptive study was carried out at the Faculty of Medical Sciences of Moron, Ciego de Avila, Cuba, during the months of March to April 2021. Theoretical and empirical methods were used, carrying out an analysis of the documents of the study plans of the Stomatology specialty for the elaboration of the program. Results: the proposed course was structured in 60 hours, for seven weeks, face-to-face and divided into five topics, enabling the general training of Stomatology undergraduate students, through the development of theoretical and care skills. Conclusions: an elective course program was developed that favors the enhancement of curricular actions, contributing to the teaching-care development of Stomatology undergraduate students.